Analyzing Gender Gap in Recognition of IPRs of Women in the Indian Handloom Sector - Verma, Saumya (Christ University Law Journal, 2025)
The 1948 Universal Declaration of Human Rights covers intellectual property rights in Article 27. It says people may protect their scientific, literary, and creative achievements. Handicrafts provide income for women, particularly in rural regions with few economic options. Women make up 16.2% of inventors worldwide in 2023, while males make up 83.8%. The United States of America has progressed as there is a considerable rise in women author registrations. The percentage of women writers registered in 2020 was above 38%, up from 28% in 1978. However, women are underrepresented in intellectual production and face prejudice, bias, and stereotypes. Arts, crafts, literature, and the handloom sector might struggle to establish intellectual property rights owing to their perceived lack of originality or marketability for legal reasons. Traditional civilizations stigmatize women who engage in these pursuits, making it hard to copyright their artistic creations. It is often observed that men have patented women’s innovations and creativity under their names. This paper advocates recognition of IPR for handloom women craftsmen. It encourages creative freedom beyond gender prejudice, fair recompense for women craftsmen.